Using in situ cosmogenic radionuclide geochemistry to characterize millennial scale denudation rates and chemical weathering rates on the Colorado Front Range - Garber, Jonathan, author; Wohl, Ellen, advisor; Rathburn, Sara, committee member; Niemann, Jeffrey, committee member; Riebe, Clifford, committee member (Colorado State University. Libraries, 2013)
Multiple authors have delineated the Colorado Front Range (COFR) landscape into distinct elevational zones with respect to contemporary geomorphologic processes, landscape development, and sediment dynamics in bedrock canyons. Several studies have estimated denudation rates using rates of post-fire erosion, alpine soil erosion, beaver dam sedimentation, and cosmogenic tor erosion, but comparison is limited due to differences in the time scale captured by different measurements. I address this gap by using cosmogenic 10Be to measure denudation rates in three process domains: flat Front Range summits, five unglaciated watersheds above the latest Pleistocene terminal glacial moraine, and five watersheds below the moraine. Two paired bedrock outcrop and soil samples were taken on flat summits in Rocky Mountain National Park. Bedrock samples were taken from a low-lying bedrock outcrop and large boulder with accompanying colluvial soil samples from the surrounding surface. Fluvial sediment was collected for 10Be analysis from the outlets of 10 watersheds. I also conducted soil surveys in each basin to examine relationships between physical characteristics, depth of regolith, and hillslope position. Low outcrops and regolith from a glacial col saddle are denuding at four times the rate of previously published tor data, while regolith from a summit flat is eroding much more slowly and at similar rates to summit flats elsewhere in the Rockies. Basins are denuding at similar rates to cosmogenic radionuclide (CRN)-derived, basin-averaged rates in the Boulder Creek watershed and show no difference between hydroclimatic process domains. Basin morphometric parameters are not significantly related to these denudation rates. The denudation rates span into the Late Pleistocene, and are an order of magnitude lower than Holocene sedimentation rates. This implies a large increase in Holocene COFR erosion in basins not glaciated during the Pleistocene, and could reflect stronger monsoonal rain systems generating more debris flows. Denudation rates increase with the percent of coarse material processed, alluding to grain size dependency of CRN concentrations. This pattern appears to be affected by valley confinement at the sampling location. Regolith is deeper and shows a more typical pattern along hillslope fall lines on upper basins, implying that weathering rates may be higher and disturbance less frequent. Bulk geochemistry of bedrock and regolith on Big Horn Flats contains the signal of Zr-rich dust inputs that may indicate the importance of Mojave Desert source areas during the Pleistocene. Millennial-scale weathering rates assuming no dust deposition (5.8 - 10 t/km2yr) are similar to modern estimates, but uncertainty from dust inputs cannot be constrained.
Keywords: Colorado; geochemical mass balance; Front Range; cosmogenic